Search For Non-Medical Treatment By Hemodialysis Patients With Chronic Renal Failure And Psychiatric Patients - Gür, Hatice; Özkan, Aysen (Fırat University, 2002)
Aim: It is of common knowledge that quite a few patients with medical illness look for non-medical treatments. There istatistiksel very few literature regarding the reason for this search and the kind of non-medical treatment they receive. In this research, we aimed to study the frequency of search for non-medical treatment, the reasons and the kind of methods used for non-medical treatments in patients with chronic renal failure who received hemodialysis and in psychiatric patients. Materyal Methods: 199 hemodialysis and 122 psychiatric patients filled out a questionnaire regarding these issues. Results: Results showed that non-medical treatment search was more frequent among psychiatric patients. In both groups helpless was the common reason for this search. Conclusion: It was who appearance that at times physicians made patients to appeal to non-professionals. Second thought should be given to health care and education in Turkey when quite few patients with even a fatal illness like renal failure search for non-medical treatments.

Amaç: Tıbbi hastalıkların tedavileri için hekim dışı başvuruların olduğu bilinmektedir. Hastaların başvuru nedenleri, ne tür tedavi aldıkları ile ilgili yayınlar oldukça kısıtlıdır. Biz bu çalışmada diyaliz hastaları ve psikiyatri hastalarında tedavi için hekim dışı başvuruların ne sıklıkta olduğunu, kimlerin daha çok başvurduğunu, başvuru nedenini ve nasıl bir yöntem uygulandığını araştırmayı amaçladık. Gereç ve yöntem: Yüz on dokuz diyaliz ve 122 psikiyatri hastasına araştırmacılar tarafından geliştirilen anket formu uyguladık. Bulgular:Psikiyatri hastalarında hekim dışı başvurunun daha sık olduğunu saptadık. Her iki grupta da en sık başvuru nedeninin çaresizlik olduğunu gördük. Sonuç: Ölümcül bir hastalık olan böbrek yetmezliğinde de, tedavi amacıyla tıp dışı başvuruların olması, bize Türkiye'de sağlık sorunlarının hala güncel olduğunu ve halka sağlık konuları ile ilgili daha ayrıntılı bilgi verilmesi gerektiğini göstermiştir.
KRONİK BÖBREK YETMEZLİĞİ OLAN DİALİZ HASTALARI İLE PSİKİYATRİ HASTALARINDA TIP DIŞI TEDAVİ ARAYIŞLARI